Penguasaan Konsep Mahasiswa pada Materi Fotosintesis : Korelasinya dengan Kemampuan Representasi pada Vertical Translations across Level - Any Fatmawati; Husnul Jannah (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Mastery of concepts and representational skills are competencies needed by students in the 21st century. One indicator of a person having representational abilities is being able to interpret scientific phenomena vertically (Vertical Translations across Level (VTL). The aims of this study are to: 1) describe student representation ability on photosynthetic material; and 2) knowing the correlation between students' conceptual mastery and their representational ability in interpreting scientific phenomena, especially photosynthetic material. The research method is correlational analysis between concept mastery and representation ability. The research subjects were 37 students who had taken Plant Physiology courses at the Biology Education Study Program, FSTT, Mandalika Education University in the even semester of the 2018/2019 academic year. Data were collected using a validated essay test. Data analysis used regression test at a significance level of 5%. The results showed that: 1) students were able to explain the process of photosynthesis using representations, and 2) there was a correlation between concept mastery and students' representational abilities in interpreting scientific phenomena vertically (VTL) on photosynthetic material. is 60.8%.